New paradigms in cell adaptation: decades of discoveries on the CrRLK1L receptor kinase signalling network. Issue 3 (7th September 2021) - Zhu, Sirui; Fu, Qiong; Xu, Fan; Zheng, Heping; Yu, Feng
Summary: Receptor‐like kinases (RLKs), which constitute the largest receptor family in plants, are essential for perceiving and relaying information about various environmental stimuli. Tremendous progress has been made in the past few decades towards elucidating the mechanisms of action of several RLKs, with emerging paradigms pointing to their roles in cell adaptations. Among these paradigms, Catharanthus roseus receptor‐like kinase 1‐like ( Cr RLK1L) proteins and their rapid alkalinization factor (RALF) peptide ligands have attracted much interest. In particular, FERONIA (FER) is a Cr RLK1L protein that participates in a wide array of physiological processes associated with RALF signalling, including cell growth and monitoring cell wall integrity, RNA and energy metabolism, and phytohormone and stress responses. Here, we analyse FER in the context of Cr RLK1L members and their ligands in multiple species. The FER working model raises many questions about the role of Cr RLK1L signalling networks during cell adaptation. For example, how do Cr RLK1Ls recognize various RALF peptides from different organisms to initiate specific phosphorylation signal cascades? How do RALF‐FER complexes achieve their specific, sometimes opposite, functions in different cell types? Here, we summarize recent major findings and highlight future perspectives in the field of Cr RLK1L signalling networks.